2018
DOI: 10.1007/s11004-018-9760-z
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Dependent Adaption of the Wiener Filter for the GPS Position Time Series

Abstract: Various methods have been used to model the time-varying curves within the global positioning system (GPS) position time series. However, very few consider the level of noise a priori before the seasonal curves are estimated. This study is the first to consider the Wiener filter (WF), already used in geodesy to denoise gravity records, to model the seasonal signals in the GPS position time series. To model the time-varying part of the signal, a first-order autoregressive process is employed. The WF is then ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The equatorial bulge in white noise amplitudes remains visible, with a minimum of 2.0 mm near the poles and a maximum of about 4.0 mm at the equator. This bulge was originally pointed out by Williams et al (2004) but was also more recently observed in IGS station position time series by Klos et al (2019). Williams et al (2004) suggested that the origin of this bulge could reside in mis-modeling of the atmospheric delays affecting GNSS observations.…”
Section: Spatial Variability Of Variance Componentsmentioning
confidence: 63%
“…The equatorial bulge in white noise amplitudes remains visible, with a minimum of 2.0 mm near the poles and a maximum of about 4.0 mm at the equator. This bulge was originally pointed out by Williams et al (2004) but was also more recently observed in IGS station position time series by Klos et al (2019). Williams et al (2004) suggested that the origin of this bulge could reside in mis-modeling of the atmospheric delays affecting GNSS observations.…”
Section: Spatial Variability Of Variance Componentsmentioning
confidence: 63%
“…A clean audio file fetched from the audio datastore is corrupted with a noisy segment extracted from the noise signal. These signals are plotted in the fig 5. Then these signals are passed to the network model and then model is trained.…”
Section: Fig 5 Fully Connected Networkmentioning
confidence: 99%
“…Wiener filter 20,21 is a linear time invariant system, which is usually used to extract useful signals contaminated by noise. The filter is realized by the minimum mean square error criterion, and the filter coefficient can be adjusted adaptively according to the input signal.…”
Section: Kalman Filter Innovation Algorithmmentioning
confidence: 99%